User satisfaction evaluation of an educational distance-learning platform with MUSA methodology - Manikaros, Nikos; Avgerinos, Evgenios; Vlachou, Roza (American Journal of Education and Learning, 2023)
The purpose of this study was to provide an exhaustive analysis of user satisfaction regarding Moodle, an online educational platform, employing an innovative approach through Multicriteria Satisfaction Analysis (MUSA). Contrary to the traditional methods of assessing parameters like Ease of Use and Effectiveness, our study considered unique criteria including Technical Dimension, Possibilities of Teachers/Participants, Pedagogical Dimension, and Automated Functions. The distinctiveness of our approach was amplified by the application of MUSA for criteria weight selection, deviating from the conventional Pairwise Comparison methodology and its reliance on extensive questionnaire administration. Our methodology encompassed the distribution of online questionnaires via Google Forms to a sample of 100 participants from Greece, focusing on the bespoke criteria to derive a holistic perspective of user satisfaction. The MUSA algorithm was instrumental in not only delineating the analytical satisfaction evaluation but also in formulating a structured improvement action plan for the educational platform. A noticeable variance in criteria weight selection was observed when juxtaposing the MUSA algorithm and the traditional Pairwise Comparison methodology, underscoring the precision and reliability of our approach. The findings emanating from the application of MUSA underscore its potential as a pivotal tool in enhancing the quality and user satisfaction of educational platforms. Practical implications of the study are profound for software developers and educational institutions alike. The integration of MUSA into the design and evaluation process of educational software promises a pathway to incessant refinement, aligning with the dynamic needs of educators and learners, thereby elevating the educational experience to unprecedented heights.